2018
DOI: 10.33122/ijtmer.v1i1.11
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Mathematics Teaching Material Based on Ethnomathematics

Abstract: The study aims to know the effectiveness of mathematics teaching material used based on ethnomathematics toward mathematical solving problem skill and student critical thinking and to know how student activity on mathematics learning by applying mathematics teaching material based on ethnomathematics. Research method applies a quantitative method with post-test only control design research type. Sampling technique applies cluster random sampling. Data collection technique applies documentation, observation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 13 publications
1
35
0
17
Order By: Relevance
“…The use of batik jambi as a learning resource in the student worksheet makes student more interested in learning, so learning is more effective. This is consistent with the results of research conducted by Imswatama & Lukman, (2018)which shows that ethno-mathematics is effective in improving student learning outcomes in mathematics.…”
Section: Figure 3: Some Student Workheet Based On Discovery Learningsupporting
confidence: 91%
“…The use of batik jambi as a learning resource in the student worksheet makes student more interested in learning, so learning is more effective. This is consistent with the results of research conducted by Imswatama & Lukman, (2018)which shows that ethno-mathematics is effective in improving student learning outcomes in mathematics.…”
Section: Figure 3: Some Student Workheet Based On Discovery Learningsupporting
confidence: 91%
“…Education is an effort that can improve human dignity and preparedness to face every change towards a better life. Education is very important, given that education is a pillar of national development (Imswatama, 2018;Usmadi, 2018;Amalia, 2018). Education is basically a conscious effort to develop students' potential by encouraging and facilitating learning activities.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the students were asked to discuss it with their group members and finally communicate the result to the researcher. The construction of geometry concepts with concrete building models is an important part in understanding geometry (Dewi, Hakim, Setiawan, Adhisuwignjo, & Rohadi, 2018;Imswatama & Lukman, 2018;Sutiarso, Coesamin, & Nurhanurawati, 2017) revealed that the investigation of the properties of geometry and concrete shape is an important part in understanding geometry. The results of their research prove that the teaching media can help students understand concepts in geometry.…”
Section: Phase-4mentioning
confidence: 99%